(3hSjdI GdoeQjO GdUGOb dehdGg GdNGdbs - (3LGeY GdGej GdSYOj GdTGaYj GdaJhMjs
(3ChdgG (B:s
(3Gddge EfG fSCdc Cf JcTa dfG Yf eYGfj CSeGFc s
(3BNQgG (B:s
(3hGdbGFe HMbjbI GdYHhOjI MbjbI GdMb GdoeJfRgI Yf GdbjO Je GdMRH GdeHGQc HMeO Gddg s
(3HBNQg aGFOgs
(3eUOQ GbJfGA GdCUd (B:s
(3djHjG (B- (3ecJHI GdChbGa HWQGHdS GdZQH (B(35) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs